Control mechanism of small organic molecules on methane adsorption capacity of coal. (1st January 2023) - Peng, Xianqi; Ji, Huaijun
Highlights: Influence of small organic molecules on methane adsorption of coal was analyzed. Change of coal pore by small organic molecules was discussed. Control mechanism of small organic molecules on coal adsorption was revealed. Abstract: Small organic molecules have a significant influence on methane adsorption of different rank coals. To explore the control mechanism of small organic molecules on methane adsorption capacity of coal, in this paper, based on the relative content of small organic molecules in different rank coals obtained by extraction experiment, the complex models of raw and residual coal with different ranks were constructed. The influence of small organic molecules on the methane adsorption of coal was analyzed by molecular simulation calculation. The control mechanism of small organic molecules on the methane adsorption capacity of coal was further discussed. The results showed that for the low-rank coal with high content of small organic molecules, small organic molecules mainly play the role of blocking and separating so that separate the larger coal pores into more micropores, thereby the methane adsorption capacity of coal pores is increased. For the middle-rank coal with the same high content of small organic molecules, micropores are closed by small organic molecules, so that its methane adsorption capacity is reduced. For the high-rank coal, due to its low content of small organic molecules, few pores are blocked or closed, that the existence of small organic molecules has no significant effect on its methane adsorption capacity. The research results help to reveal the microscopic mechanism of methane adsorption of coal, which has great significance to the development of coalbed seam gas and mine gas disaster prevention.